In silico investigation of the impact of synonymous variants in ABCB4 gene on mRNA stability/structure, splicing accuracy and codon usage: Potential contribution to PFIC3 disease. (December 2016) - Khabou, Boudour; Siala-Sahnoun, Olfa; Gargouri, Lamia; Mkaouar-Rebai, Emna; Keskes, Leila; Hachicha, Mongia; Fakhfakh, Faiza
Graphical abstract: Highlights: We reported the first molecular diagnostic of PFIC3 in Tunisia. The first bioinformatic exploration of synonymous SNPs in ABCB4 gene. Potential implication of the c.175C > T variant in an aberrant splicing. The c.504C > T variation seems to affect the predicted mRNA stability. Abstract: P rogressiveF amilialI ntrahepaticC holestasis type3 (PFIC3) is an autosomal-recessive liver disease due to mutations in the ABCB4 gene encoding for the MDR3 protein. In the present study, we performed molecular and bioinformatic analyses in PFIC3 patients in order to understand the molecular basis of the disease. The three studied patients with PFIC3 were screened by PCR amplification followed by direct sequencing of the 27 coding exons of ABCB4. In silico analysis was performed by bioinformatic programs. We revealed three synonymous polymorphisms c.175C > T, c.504C > T, c.711A > T respectively in exon 4, 6, 8 and an intronic c.3487-16T > C variation in intron 26. The computational study of these polymorphic variants using Human Splicing Finder, ex-skip, Mfold and kineFold tools showed the putative impact on the composition of the cis -acting regulatory elements of splicing as well as on the mRNA structure and stability. Moreover, the protein level was affected by codon usage changes estimated by the calculation of ΔRSCU and ΔLog Ratio of codon frequencies interfering as consequence with the accurate folding of the MDR3 protein. As the first initiative of the mutational study of ABCB4 genes in Tunisia, our results are suggestive of a potential downstream molecular effect for the described polymorphisms on the expression pattern of the ABCB4 underlining the importance of synonymous variants.